Primary Metabolites, Anthocyanins, and Hydrolyzable Tannins in the Pomegranate Fruit - Bar-Ya'akov, Irit; Tian, Li; Amir, Rachel; Holland, Doron (Frontiers in Plant Science, 2019)
Pomegranate (Punica granatum L.) is an important and interesting fruit tree that is cultivated in many parts of the world. In recent years, along with the increase in its cultivation and consumption there has been a dramatic increase in the scientific interest in its biology, methods of cultivation, adaptation to environmental cues and its health-promoting properties. Quite a large proportion of the various metabolites produced in the pomegranate were determined and their content in the bark, roots, leaves, and fruit was reported. Many reviews on polyphenolic compound content, antioxidant activity and health-promoting compounds were published recently. However, only very few recent reports were dedicated to primary metabolites, despite the fact that much work was done on organic acids, sugars, proteins, lipids, and amino acids of the pomegranate fruit. In this review, a special effort was made to present these recent studies and the review is devoted to primary metabolites. The reported data show high variation in the content of primary metabolites within the pomegranate fruit; therefore the data is presented (whenever possible) according to fruit tissues (peel, arils, and seeds), developmental stages of the fruit, environmental and climatic conditions, and genetic background. Most of the data on pomegranate is based on metabolic content and contains no genetic or molecular analysis except for work done on anthocyanins and hydrolyzable tannins. In those cases, gene assignment and genetic control studies were pointed out in the review. The recent publication of the genome sequences from several pomegranate varieties and transcriptomic data from fruits, flowers, and leaves is expected to facilitate the understanding of genetic control of metabolites in pomegranate.